DINAMIKA KURIKULUM DAN PERKEMBANGAN KELEMBAGAAN MADRASAH DI INDONESIA - Dessiyana Septiani; Erin Nada Nur Nadiyah; Sutrimo Purnomo (EL ROBIH: Jurnal Pendidikan Madrasah Ibtidaiyah, 2026)
This study analyzes the dynamics of curriculum development and the institutional progress of madrasahs in Indonesia. Madrasahs have experienced continuous transformation influenced by social, cultural, political, and educational changes occurring in society. The curriculum implemented in madrasahs has evolved from a traditional religious learning orientation toward a more integrated educational system that combines Islamic values with general sciences. Various curriculum reforms were introduced to align madrasah education with national education standards, technological advancement, and the growing demands of globalization. In addition, institutional development has been carried out through improvements in educational management, teacher quality, learning facilities, and administrative systems to strengthen the competitiveness of madrasahs within the national education framework. This research applies a literature review method by examining books, academic journals, and other relevant scientific sources related to curriculum and institutional development in madrasahs. The findings reveal that curriculum dynamics and institutional transformation have significantly contributed to enhancing the role of madrasahs as Islamic educational institutions capable of adapting to modern educational challenges. Nevertheless, madrasahs still face several obstacles related to educational quality, modernization, and policy implementation in maintaining their relevance and sustainability in Indonesia’s educational system.